Analisis Prioritas Belanja Desa Pada Dana Desa Kayu Bawang Kabupaten Banjar - Rakhmatullah; Ruddy Syafruddin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
This research aims to (1) find out the village expenditure in the Kayu Bawangvillage fund in Banjar Regency, and (2) find out the priority of village spending on theright village fund in developing Kayu Bawang Village, Banjar Regency.The Respondents in this study were six respondents who were consideredinfluential in determining village spending in Kayu Bawang Village, which was used indata processing by using AHP(Analytical Hierarchy Process).This study's results indicate that the alternative criteria for RPJMDes, VillagePotential, and Village Problems influence the determination of village expenditurepriorities in the order of preference value of 54% RPJMDes, 30% Village Problems,and 16% Village Potential. Based on these alternative criteria, the preference forvillage development priorities is 42%, community empowerment is 32%, communitydevelopment is 20%, and village administration is 6%. With the most dominantconclusion, village development is 42%.